PENGETAHUAN EKOLOGI MASYARAKAT LOKAL DALAM PEMILIHAN POHON PELINDUNG PADASISTEM AGROFORESTRI TRADISIONAL "DUSUNG" PALA DI AMBON - Messalina Lovenia Salampessy (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
Local ecological knowledge is closely linked to decision-making process for planting tree. The aims of this study are to describe and explain local community’s decision-making process in the selection of shading trees on their lands according to their understanding and knowledge. This study used case study approach. Data was collected through in-depth interviews and observations. The results of the study showed that to manage traditional agroforestry, the community planted nutmeg (Myristica fragrans) as the main crop species and selected the covering trees, such as walnuts (Canarium sp.) and durian (Durio sp.). The reasons in selecting shading trees were as follows: the suitability of biophysical condition; supporting nutmeg growth; ease of maintenance and harvesting activities; parental inheritance; yield diversity; and ease of marketing activities. Learning from the study, the government and relevant stakeholders are expected touse local ecological knowledge to support the development of community forestry.